2014
DOI: 10.2478/ijnaoe-2013-0208
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and production quality of hand-layup and vacuum infusion processed hybrid composite materials for GFRP marine structures

Abstract: Glass Fiber Reinforced Plastic (GFRP) structures are primarily manufactured using hand lay-up or vacuum infusion techniques, which are cost-effective for the construction of marine vessels. This paper aims to investigate the mechanical properties and failure mechanisms of the hybrid GFRP composites, formed by applying the hand lay-up processed exterior and the vacuum infusion processed interior layups, providing benefits for structural performance and ease of manufacturing. The hybrid GFRP composites contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 13 publications
2
41
0
Order By: Relevance
“…It reveals that there is a statistically significant difference in flexural strength and tensile modulus of EPSF and EPELO10SF composites. Further, in flexural strength and tensile modulus properties, the between‐group variance was higher than the within‐group variance which indicated the significant difference in the properties of specimens . Due to the nature of the hand lay‐up process and presence of voids, this statistical variance is observed in mechanical properties.…”
Section: Resultsmentioning
confidence: 92%
“…It reveals that there is a statistically significant difference in flexural strength and tensile modulus of EPSF and EPELO10SF composites. Further, in flexural strength and tensile modulus properties, the between‐group variance was higher than the within‐group variance which indicated the significant difference in the properties of specimens . Due to the nature of the hand lay‐up process and presence of voids, this statistical variance is observed in mechanical properties.…”
Section: Resultsmentioning
confidence: 92%
“…Kim et al. 6 showed that vacuum infusion-processed glass fiber-reinforced plastics have higher average ultimate strength and modulus than the same materials processed by hand layup, in both tension and compression tests. They attributed this improvement to the higher fiber volume fraction of the vacuum infusion processed samples.…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturing imperfections, like air inclusions, de-cohesions and fiber misalignment, and chemical features, i.e., the influence of ambient and laminate temperature while curing and humidity, may seriously affect the composite strength as well as its failure modes. This aspect is widely covered in literature and confirmed in recent works by Godani et al (2014) and Kim et al (2014), who investigated the mechanical properties and failure mechanisms of the GFRP composite materials including the hand lay-up processed, the vacuum infusion processed and the hybrid GFRP composites, particularly focusing on interlaminar strength and buckling induced delaminations. Kalantari et al (2017) studied the effects of three sources of uncertainties, namely, existence of matrix voids, fiber misalignment and thickness variation, on optimal and robust designs, with the main focus being the influence of matrix voids.…”
Section: Mechanical Aspects and Current Design Practicementioning
confidence: 63%